Nitrogen plasma passivation of GaAs nanowires resolved by temperature dependent photoluminescence. (1st December 2022) - Irish, Austin; Zou, Xianshao; Barrigon, Enrique; D'Acunto, Giulio; Timm, Rainer; T Borgström, Magnus; Yartsev, Arkady
Abstract: We demonstrate a significant improvement in the optical performance of GaAs nanowires achieved using a mixed nitrogen-hydrogen plasma which passivates surface states and reduces the rate of nonradiative recombination. This has been confirmed by time-resolved photoluminescence measurements. At room temperature, the intensity and lifetime of radiative recombination in the plasma-treated nanowires was several times greater than that of the as-grown GaAs nanowires. Low-temperature measurements corroborated these findings, revealing a dramatic increase in photoluminescence by two orders of magnitude. Photoelectron spectroscopy of plasma passivated nanowires demonstrated a yearlong stability achieved through the replacement of surface oxygen with nitrogen. Furthermore, the process removed the As 0 defects observed on non-passivated nanowires which are known to impair devices. The results validate plasma as a nitridation technique suitable for nanoscale GaAs crystals. As a simple ex situ procedure with modest temperature and vacuum requirements, it represents an easy method for incorporating GaAs nanostructures into optoelectronic devices.